Organic Syntheses 2003
DOI: 10.1002/0471264180.os045.28
|View full text |Cite
|
Sign up to set email alerts
|

9‐Phenylphenanthrene

Abstract: 9‐Phenylphenanthrene reactant: 2.56 g. (0.01 mole) of triphenylethylene product: 9‐phenylphenanthrene

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Large-Scale Synthesis of Intermediates 5 and 9. The high-yielding Green-Rowe oxidation procedure, [26][27][28] as used in the research synthesis of 4 (Scheme 1), was judged critical for scale-up: DSC measurements showed that deprotonation of 3 with potassium hydroxide in ethanol solution at 60 °C occurred at the onset temperature of the exothermic decomposition of the aci-nitroanion intermediate 13 29,30 (Scheme 2, estimated TMR < 30 min at 60 °C). Furthermore, the combination of ethanol and excess sodium hypochlorite is a source for ethylhypochlorite, which is both volatile (bp 36 °C) and explosive.…”
Section: Research Syntheses Of Pde472mentioning
confidence: 99%
“…Large-Scale Synthesis of Intermediates 5 and 9. The high-yielding Green-Rowe oxidation procedure, [26][27][28] as used in the research synthesis of 4 (Scheme 1), was judged critical for scale-up: DSC measurements showed that deprotonation of 3 with potassium hydroxide in ethanol solution at 60 °C occurred at the onset temperature of the exothermic decomposition of the aci-nitroanion intermediate 13 29,30 (Scheme 2, estimated TMR < 30 min at 60 °C). Furthermore, the combination of ethanol and excess sodium hypochlorite is a source for ethylhypochlorite, which is both volatile (bp 36 °C) and explosive.…”
Section: Research Syntheses Of Pde472mentioning
confidence: 99%